2020
DOI: 10.1186/s13014-020-01674-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness analysis of nimotuzumab for the radiotherapy of locoregionally advanced nasopharyngeal carcinoma

Abstract: Background This study aimed to assess the effectiveness and cost-effectiveness of nimotuzumab in patients with locoregionally advanced nasopharyngeal carcinoma (LA-NPC). Methods LA-NPC patients treated between October 2013 and December 2016 were retrospectively reviewed. A well-balanced cohort of patients who received nimotuzumab in addition to standard treatment (n = 50) and patients who did not receive nimotuzumab (n = 100) was selected using propensity score-matching method (1:2 ratio) for the cost-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
20
1
Order By: Relevance
“…Fujian Province has carried out screening for nasopharyngeal cancer for long time. The precise treatment can reduce the cost of treatment and improve the survival rate of patients [22]. For females, the incidence rate of breast cancer is the highest in both areas.…”
Section: Discussionmentioning
confidence: 99%
“…Fujian Province has carried out screening for nasopharyngeal cancer for long time. The precise treatment can reduce the cost of treatment and improve the survival rate of patients [22]. For females, the incidence rate of breast cancer is the highest in both areas.…”
Section: Discussionmentioning
confidence: 99%
“…All chemotherapy regimens were administered according to a previously described protocol [ 13 ]. Patients with stage I disease received radiotherapy alone.…”
Section: Methodsmentioning
confidence: 99%
“…All patients received intensity-modulated radiotherapy (IMRT), and the target volume and dose of radiotherapy were calculated using a previously described treatment protocol [ 13 , 14 ]. In brief, the planning target volumes obtained for the primary gross tumor volume or gross tumor volume in the involved lymph nodes were exposed to a total dose of 70 Gy in 31–35 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al (29) found that nimotuzumab plus CCRT for locally advanced nasopharyngeal carcinoma can signi cantly improve the 3-year OS, compared with CCRT alone (98.0% vs. 91.0%, P = 0.032). Marta et al…”
Section: Adverse Eventsmentioning
confidence: 99%